Implementasi Media Pemasaran Digital Marketing Untuk Meningkatkan Kedatangan Konsumen Akomodasi Pariwisata Pada Pandawa Guest House Lembongan - Putra, I Wayan Restu Aditya; Putranti, Made Irma Dwi; Putri, ⁠⁠I Gusti Agung Prabandari Tri (Journal Of Human And Education (JAHE), 2025)
The creation of digital marketing media such as Landing Page, Google Business and Instagram marketing content aims to increase the number of tourist visits to the Pandawa Guest House Lembongan tourism accommodation. The research methods used in this study include preparation and analysis of needs, data collection, creation of digital marketing media and assistance in managing marketing media and evaluation. The results of the study show that digital marketing media can be an effective and efficient marketing media due to its very wide market reach and easy use. Digital marketing media not only provides benefits for Pandawa Guest House Lembongan business owners but can also provide convenience for prospective tourists who want to find information related to accommodation accurately and reliably. The evaluation shows that there has been an increase in tourist visits to Pandawa Guest House Lembongan.